Racial Differences in Retention in a Community-based Addiction Reduction Program Implemented by Peer Recovery Coaches for Women of Reproductive Age - Anastasiya Yakovlyeva BS; Wilma Griffin MS; Allison Worden BS; Sarah Roth MPH, MHA; Paige DeChant BS; Dawn Butler JD, MSW; Qing Tang MS; Debra K. Litzelman MD, MA (SAGE Publishing, 2023)
To identify program characteristics that influence the retention of women of reproductive age in the C ommunity-based A ddiction Re duction program (CARE), mixed-method analyses of CARE survey data and CARE Peer Recovery Coach (PRC) narrative entries of participant encounters were performed. About 251 women were enrolled in this prospective community-based implementation science intervention. We compared survey responses by race for treatment status, treatment motivation scales, and retention in the program at intake, 2-, 6-, 9-, and 12-month follow ups using Chi-square/ T -tests. Qualitative analysis of PRC narrative entries was conducted following thematic analysis and crystallization immersion analytic methods. White compared with Black women in CARE were significantly more likely to be in treatment at intake ( P  < .001) and more motivated to engage in recovery treatment ( P  < .001). However, Black women were retained longer in CARE at 2- ( P  < .006), 6- ( P  < .011), and 9- ( P  < .004) months. PRC narrative entries were coded, and emergent themes mapped well to the 4 types of supports provided by PRC as outlined by the Substance Abuse and Mental Health Services Administration: emotional, instrumental, informational, and affiliational. Analysis of narrative entries by race revealed that Black women were given more detailed information, communications with PRC were more encouraging and proactive in identifying and meeting needs, and PRC took a more hands-on approach when assisting and linking to resources. The inclusion of PRC as integral members of SUD recovery programs may preferentially provide Black women with SUD the opportunity to build more trusting relationships with these peer coaches, thereby increasing their participation and retention.